Optimizing Social Support: Building Resilience to Work-Related Stress in Women through Managing Conflict Between Work and Personal Life - Jadmiko, Purbo; Azliyanti, Elfitra (Jurnal Ekonomika Dan Bisnis (JEBS), 2023)
Job stress, as a major well-being issue in the contemporary world of work, is attracting increasing attention from researchers, especially in the context of its effects on women. Women often fulfill dual roles as professional workers and household leaders, presenting unique challenges in managing multiple demands both at work and within the family sphere. This research discusses how the imbalance between work life and personal life, especially work-life conflict, influences work stress levels in career women. This research involved 200 women who had worked for at least 6 months. Using the Structural Equation Modeling (SEM) data analysis method with the help of the SmartPLS application, this research discusses the influence of Work-Life Conflict (WLC) on women's work stress levels. The findings highlight the importance of conflict management between work and personal life, with implications for organizational policies in supporting such balance. Although Perceived Social Support (PSS) was not proven to be a significant mediator, this research contributes to the understanding of the complexity of the dynamics between these variables, providing a basis for further research and practical implementation. These findings also emphasize the important role of leadership in creating an organizational culture that supports work-life balance.